RELATIONSHIP KNOWLEDGE AND COMMUNITY BEHAVIOR IN APPLYING SOCIAL DISTANCE AS ONE OF THE COVID-19 PREVENTION MEASURES. - Dorcia TN Yabiy; Parti Parti; Saktiawati Saktiawati; Eki Nawang Wulandari (Universitas Islam Negeri Alauddin Makassar, 2021)
Background:Covid-19 can spread from person to person people through splashes from the nose or mouth which comes out when people who contract Covid-19 cough or exhale. People most at risk contracting this disease is a person who is in close contact with Covid-19 patients including those who treat. Objective:Covid-19 has been declared a pandemic world by WHO (WHO, 2020). Nationally it has been specified status of disaster emergency outbreak of disease due to Coronavirus in Indonesia.Method:The design of this study is a cross-sectional study with non-sampling techniques probability sampling is purposive sampling. Sample in this study, there were 50 people.Result: the results of the study showed that many respondents have a good knowledge category 44 people, and have positive behavior that's as many as 40 people. Next, the results of the analysis using fisher's exact test obtained results p = 0.000 (< 0.05) which means there is a relationship between knowledge and behavior of the community in applying social distance as a precautionary measure Covid-19.Conclusion:From the results of the study it can be concluded that there is a relationship between knowledge and community behavior in applying social distance as one of the Covid-19 prevention measures in Bawalipu Village